'Activity-silent' working memory in prefrontal cortex: a dynamic coding framework. Issue 7 (July 2015) - Stokes, Mark G.
Highlights WM is thought to depend on persistent maintenance of stationary activity states. However, population-level analyses reveal that brain activity is highly dynamic. Accumulating evidence implicates activity-silent neural states for WM. Dynamic coding suggests that WM is encoded in patterns of functional connectivity.